Lipase Biosynthesis by Aspergillus niger Utilizing Solid Waste as Feedstock: Advancing a Circular Bioeconomy Approach - Nigam, Mohit; Srivastava, Vaibhav; Gautam, Virangana; Tripathi, Tripti; Dubey, Saijasi; Awasthi, Garima (Journal of Neonatal Surgery, 2025)
Lipase production was carried out using agro-industrial residues mustard oil cake (MC), wheat straw (WS), and olive oil (OO) as substrates in submerged fermentation by Aspergillus niger. Two concentrations (1.2% and 2.4% w/v) were tested for each substrate. The highest enzyme activity was observed with mustard oil cake at 2.4% (MC2), reaching 480 U/mL after 72 hours of incubation, followed by 450 U/mL for olive oil at 2.4% (OO2) and 360 U/mL for wheat straw at 2.4% (WS2). A continuous decrease in glucose concentration confirmed substrate utilization, with maximum consumption in MC1. Protein concentration peaked at 8.1 mg/mL in MC2 at 72 h, suggesting efficient enzyme synthesis. Purification of the enzyme through ammonium sulfate precipitation (80% w/v) followed by ion exchange chromatography increased the specific activity significantly, reaching 415.14 U/mg for MC2. The percentage yield after salting-out was highest for MC2 (361.11%), indicating the effectiveness of this substrate. Overall, mustard oil cake outperformed wheat straw and olive oil in terms of lipase yield, purification efficiency, and substrate utilization. These results demonstrate the potential of low-cost solid waste substrates in cost-effective enzyme production aligned with circular bioeconomy principles